The effect of niobium on the microstructure of ferritic stainless steel - Kuzucu, V; Aksoy, M; Korkut, MH; Yildirim, MM (Elsevier Science Sa Lausanne, 1997)
The effect of different amounts of Nb and of homogenization on the ferritic stainless steels containing 17-18 wt.% Cr was investigated with scanning electron microscopy (SEM), optical microscopy, energy-dispersive spectrometry (EDS), X-ray diffraction (XRD) and differential thermal analysis (DTA). It was observed that M23C6, NbC and sigma phase formed in these steels. In addition, the formation of Nb2C was observed in the sample containing 3.0 wt.% Nb. While the amount of Nb increased from 0.5 to 3.0 wt.% Nb, the microhardness of the matrix and the amount of M23C6 decreased and the toughness of the samples increased. After homogenization, the increase in the toughness of the samples containing 1.5-3.0 wt.%Nb was considerable and impressive. (C) 1997 Elsevier Science S.A.
Keywords: carbides; microstructure; stainless steel